If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + -1y = y + -4y Combine like terms: y + -4y = -3y -8 + -1y = -3y Solving -8 + -1y = -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. -8 + -1y + 3y = -3y + 3y Combine like terms: -1y + 3y = 2y -8 + 2y = -3y + 3y Combine like terms: -3y + 3y = 0 -8 + 2y = 0 Add '8' to each side of the equation. -8 + 8 + 2y = 0 + 8 Combine like terms: -8 + 8 = 0 0 + 2y = 0 + 8 2y = 0 + 8 Combine like terms: 0 + 8 = 8 2y = 8 Divide each side by '2'. y = 4 Simplifying y = 4
| 3x+39+2x+14=72 | | -3=-4v+5v | | 7x-5(2x+4)=16 | | -4y-2=-14 | | -1=4b+6-3b | | -2x^3+x^2+15x=0 | | 6y+7=2y+19 | | x-10=3+x/2 | | 14=9x+5+8 | | 11+x+5x=1+8x | | 2m-13=7m+27 | | 3x+39+1x+36=72 | | -v-3=3 | | 4(5y-3)-3y=5 | | 5+2.2h=-3.7 | | b+3(b)=64 | | -4m-4-8m=8-6m | | m(x)=5x-5 | | -4x+-36=-8 | | (x)=5x-5 | | 4(5y-3)-3=5 | | 8w-2=-10w-30+4 | | 33b-24b-7+24=-5 | | 46x-25y=15 | | 20y-12-3y=5 | | 2t-5=18.8 | | (3x^2+11+20)+(10x^2-21x-3)= | | (6+R)+2=2(R+2) | | 497= | | -9+8r=7(-5r-1)-2 | | 6u=21-4 | | 29p-3=45 |